The Effect of Prenatal Yoga on Anxiety in Pregnant Women in the Third Trimester Literature Review - Lubis, Rosni; Rahmawati, Rizkha; Delmaifanis, Delmaifanis; Primasari, Nina; Jehanara, Jehanara (Journal of Economics and Public Health, 2025)
Anxiety is one of the psychological disorders often experienced by pregnant women, especially in the third trimester. If left untreated, anxiety can have a negative impact on the physical and mental health of the mother and the development of the fetus. One non-pharmacological approach that is considered effective in reducing pregnancy anxiety is prenatal yoga. This study aims to examine the effect of prenatal yoga on the level of anxiety of pregnant women in the third trimester through a literature review method, referring to scientific literature from 2020 to 2025 with data sources obtained from national and international journal articles. PICOS approach, by reviewing 13 articles from various trusted sources such as Google Scholar, Semantic Scholar, Research Gate, and Garuda Kemdikbud, and selected databases that have been indexed at the national and international levels, such as Sinta 1, 2, 3, 4, Scopus, and Index Copernicus International (ICI). Based on Table 4, 13 articles showed that there was a relationship between prenatal yoga and anxiety with a value of (p = <0.05) with the most frequent practice being 4 times a month (once a week) with a duration of 60 minutes. The findings from this literature review indicate that routine prenatal yoga can reduce the level of anxiety of pregnant women, improve sleep quality, and increase emotional readiness before childbirth. In addition, prenatal yoga exercises have also been shown to improve maternal connection with the fetus, stabilize emotions, and help reduce physical stress that arises due to physiological changes during pregnancy. Prenatal yoga is one of the non-pharmacological methods that is effective in reducing anxiety levels in pregnant women in the third trimester, it is recommended that health workers, especially midwives, encourage the implementation of prenatal yoga as part of education and health promotion for pregnant women.